The development of Malaysia ICT subject school based assessment management system (SBAMS4ICT) - Abd Razak, Abd Hadi; Fadzuli, M.S.; Fairuz, M.Z. (International Association of Computer Science and Information Technology Press (IACSIT), 2013)
Curriculum Development Division (CDD) has introduced Information and Communication Technology (ICT) in 2006 as an elective subject for Malaysia Education Certificate.The Malaysia Examinations Syndicate (MSE) designed the assessment instruments based on the syllabus released by the CDD.Anyhow, the management of the assessment records by assessor on ground is still on manual effort. Assessor need fill in same data into different forms. Records need to be bind in a ring file (student’s portfolio), and placed in the locked and secured place.Increase assessors’ workload, tendency to writing error, time consuming, not updated records, and a few to mention the weakness of this approach.For that regard this project is proposed and the prototype of School Based Assessment Management System for ICT Subject has been developed.The requirements needed have been identified and the prototype development has employed Agile System Development Methodology.By using a Test Script method has tested the functionalities of the prototype. System evaluation has utilized Perceived Usefulness and Perceived Ease-of-Use instruments. The system prototype has enable assessors to manage assessment records easily compared to manual approach.School admins would have capability to monitor the assessment progress. Students will have a copy of their progress notified through email.